PUBLIC RELATIONS STRATEGY IN BUILDING BRAND IMAGE AT MOVENPICK RESORT - Rika Pratiwi; Ni Nyoman Sri Astuti; I Ketut Astawa (Journal of Applied Sciences in Travel and Hospitality, 2019)
This research aims to formulate public relations strategy in brand building the most appropriate image applied by the hotel Movenpick Resort & Spa Jimbaran in order to take advantage opportunities and anticipate existing threats by utilizing power and anticipate shortcomings. This data retrieval technique uses interviews to the Public Relation. Respondents in this study consists of 7 people, each from the public relations division, sales, human resources, DOS, front office and 2 visitors. Data analysis by using SWOT, IFAS and EFAS matrix. The results of data processing on SWOT matrix resulted in values of 2.90 and 2.95 which lie in column V of defense strategy. The next step is to carry out the steps implemented from the public structure relation in building brand image that is increase intensity and the quality of advertising promotion on online media, educate the market to find new customers with the help of media through magazines, newspapers and radio.